Bioengineering 3D Neural Networks Using Magnetic Manipulations. (9th September 2022) - Plen, Reut; Smith, Alejandra; Blum, Ofir; Aloni, Or; Locker, Uri; Shapira, Zehavit; Margel, Shlomo; Shefi, Orit
Abstract: Controlling nerve cells to form pre‐designed 3D neural networks that recapitulate the intricate neural interconnectivity in the brain is essential for developing neuronal interfaces and new regeneration approaches. Here, nerve cells within 3D biomaterials are dynamically localized using nano‐based magnetic manipulations. Nerve cells are transformed into magnetic units and their organizational layout is manipulated using external magnetic field gradients. Iron oxide nanoparticles are incorporated into both Pheochromocytoma cell‐line 12 (PC12) cells and primary mice cortical neurons and the magnetized cells are subjected to multiple magnetic fields using pre‐designed magnetic arrays. Their movement is controlled inside multi‐layered 3D collagen scaffolds, which simulate the innate properties of in‐vivo tissue structures. Via these magnetic manipulations, functional 3D microarchitectures of neural networks are created. In light of the clustered and layered structure of the mammalian central nervous system, this strategy paves the way to creating customized 3D tissue architectures for bioengineering applications, enabling a broad range of advanced implementations and providing efficient models for investigating cellular and tissue behavior. Abstract : In this work, nerve cells are transformed into magnetic units and dynamically localized within 3D biomaterials by magnetic manipulations. Their movement is controlled inside multi‐layered 3D collagen scaffolds, simulating the innate properties of in‐vivo tissue structures, thus constructing pre‐designed viable and functional 3D microarchitectures of neural networks.